Analysis of the Digital Wallet Applications, Purchasing Power on Consumer Purchase Decisions on the Shopee Platform (Study on UNP Kediri Students) - Putra Panglipur, Yerikho; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to analyze the ability of digital wallet applications and purchasing power on consumer purchase decisions on the Shopee platform. Design/Methode/Approach: This study uses a quantitative approach method, with a survey method that uses primimeter data (by making a research questionnaire form containing a statement questionnaire). This study took a sample of 30 respondents, who used a purposive sampling technique. The results of the questionnaire data were then analyzed by analyzing the classical assumption test of the multiple linear regression method. This questionnaire was filled out using a Likert scale. Research Finding: based on the results of this study, through the distribution of research questionnaires to UNP Kediri students, it is proven that the digital wallet application variable (X1) and the purchasing power variable (X2) have a significant correlation with consumer purchase decisions (Y) on the Shopee platform. Theoretical contribution/Originality: to increase understanding of digital wallet applications and purchasing power in purchasing products on the Shopee platform. Practitionel/Policy implication: improving the quality of digital wallets and exploring various other e-commerce. Research limitations: short time spans, respondents who respond less at times help fill out the questionnaire of this research.